Pengembangan Bahan Ajar Matematika Aktuaria untuk Meningkatkan Kemampuan Analisis Mahasiswa - Manullang, Sudianto (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aimed to develop teaching materials in actuarial courses at FMIPA State University of Medan to support the learning during the Covid-19 pandemic. This research used research and development method. The samples of this study were 32 students of FMIPA State University of Medan who took actuarial courses. The research instrument used in this study was pre and post test and observation sheets. The results showed that the t test was 20.64, in which the t count value was greater than the t table value (20.64> 1.462). Thus, learning using actuarial mathematics teaching materials has an effect on students' analytical skills. Hence, Ho was rejected and Ha was accepted, which means that there was significant influence of actuarial mathematics teaching materials on the students’ analytical skills at the State University of Medan.